A Tourism Village Planning Strategy Using the SOAR Model in Penglatan Village, Buleleng Regency, Bali - Wirasetia, Putu Andi; Widiastini, Ni Made Ary; Rahmawati, Putu Indah (Institut Pariwisata dan Bisnis Internasional, 2022)
Penglatan Village is one of the villages in Buleleng district which is famous for its typical food, namely dodol and the art of sound art, namely Renganis. Penglatan Village has tourism potential that has not been optimally packaged and marketed. Therefore, this study aims to explore the feasibility of Penglatan village to be developed and to analyze the tourism potential it has as a tourism village to build sustainable tourism in Buleleng Regency. This study uses a qualitative research approach. Data collection methods used were interviews, observation, documentation and FGD (Focus Group Discussion). The tourism potential includes, among others, middle culture of furniture, the